Efficiency Analysis of Surgical Services by Combined Use of Data Envelopment Analysis and Gray Relational Analysis. - Girginer, Nuray; Köse, Tunç; Uçkun, Nurullah (Journal of Medical Systems, 2015)
The aim of this study was to determine the efficiency of surgical services offered by a public hospital, to rank efficient services and to determine important factors on efficiency of services. DEA (to determine efficiency of services) and GRA (to rank efficient services and ranking of important variables in efficiency) were used in this study. DEA showed that all services were observably efficient except Cardiovascular and Plastic surgery. GRA showed that the services of Ophthalmology, Otorhinolaryngology (ENT) and Paediatric Surgery shared the first three ranks in order of decreasing frequency. Findings obtained from GRA, the most important variables in the performances of surgical services were found to be the number of patients and healthcare personnel. Findings obtained from this study are thought to help inefficient services to attain an efficient structure. When the importance of this issue regarding hospitals and the government is considered, similarly designed studies should be continually updated and revised in line with changing circumstances. When shortcomings in the existing literature are taken into account, this could be considered to be a pioneer study that will contribute to the literature and promote future studies to be conducted on this issue.